Atp6i deficient mouse model uncovers transforming growth factor-β1 /Smad2/3 as a key signaling pathway regulating odontoblast differentiation and tooth root formation - Jue Wang; Abigail McVicar; Yilin Chen; Hong-Wen Deng; Zhihe Zhao; Wei Chen; Yi-Ping Li (Nature Publishing Group, 2023)
Abstract The biomolecular mechanisms that regulate tooth root development and odontoblast differentiation are poorly understood. We found that Atp6i deficient mice (Atp6i −/− ) arrested tooth root formation, indicated by truncated Hertwig's epithelial root sheath (HERS) progression. Furthermore, Atp6i deficiency significantly reduced the proliferation and differentiation of radicular odontogenic cells responsible for root formation. Atp6i −/− mice had largely decreased expression of odontoblast differentiation marker gene expression profiles (Col1a1, Nfic, Dspp, and Osx) in the alveolar bone. Atp6i −/− mice sample RNA-seq analysis results showed decreased expression levels of odontoblast markers. Additionally, there was a significant reduction in Smad2/3 activation, inhibiting transforming growth factor-β (TGF-β) signaling in Atp6i −/− odontoblasts. Through treating pulp precursor cells with Atp6i −/− or wild-type OC bone resorption-conditioned medium, we found the latter medium to promote odontoblast differentiation, as shown by increased odontoblast differentiation marker genes expression (Nfic, Dspp, Osx, and Runx2). This increased expression was significantly blocked by anti-TGF-β1 antibody neutralization, whereas odontoblast differentiation and Smad2/3 activation were significantly attenuated by Atp6i −/− OC conditioned medium. Importantly, ectopic TGF-β1 partially rescued root development and root dentin deposition of Atp6i −/− mice tooth germs were transplanted under mouse kidney capsules. Collectively, our novel data shows that the prevention of TGF-β1 release from the alveolar bone matrix due to OC dysfunction may lead to osteopetrosis-associated root formation via impaired radicular odontoblast differentiation. As such, this study uncovers TGF-β1 /Smad2/3 as a key signaling pathway regulating odontoblast differentiation and tooth root formation and may contribute to future therapeutic approaches to tooth root regeneration.